2008
DOI: 10.1158/1055-9965.epi-08-0574
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Alterations of p16INK4a and p14ARF in Oral Proliferative Verrucous Leukoplakia

Abstract: Proliferative verrucous leukoplakia (PVL) represents a rare but highly aggressive form of oral leukoplakia with >70% progressing to malignancy. Yet, PVL remains biologically and genetically poorly understood. This study evaluated the cell cycle regulatory genes, p16 INK4aand p14 ARF , for homozygous deletion, loss of heterozygosity, and mutation events in 20 PVL cases. Deletion of exon 1B, 1A, or 2 was detected in 40%, 35%, and 0% of patients, respectively. Deletions of exons 1A and 1B markedly exceed levels r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Others were not able to detect any definitive relationship with HPV [11,12]. Kresty et al [13] described some genetic changes in these patients, and Kkanrit et al [14] reported a ploidy anomaly. Tobacco does not play a significant role in PVL [2,5,15].…”
Section: Introductionmentioning
confidence: 98%
“…Others were not able to detect any definitive relationship with HPV [11,12]. Kresty et al [13] described some genetic changes in these patients, and Kkanrit et al [14] reported a ploidy anomaly. Tobacco does not play a significant role in PVL [2,5,15].…”
Section: Introductionmentioning
confidence: 98%
“…22,23 The reduction in p16 INK4a expression, in addition to its epigenetic gene silencing, is related to mouth cancer and precancer and it is believed that its inactivation is an early and progressive event as the tumor stage and degree of dysplasia of premalignant lesions advances; at times, this is related to some of the clinical and pathologic parameters or to the expression of other cell-cycle regulatory proteins. 10,[24][25][26][27][28][29][30] In our work we found a gradual reduction in p16 INK4a expression as tumor stages advanced, although without statistically significant differences on quantitative analysis. p16 INK4a is an important marker involved in cellcycle control.…”
Section: Discussionmentioning
confidence: 68%
“…In patients with severe oral dysplasia, mutations in the p16CDKN2A gene were infrequent (Kresty et al 2002). In a subsequent study conducted by the same author, deletion of p16CDKN2A exon 2 was not detected (Kresty et al 2008). It is important to stress that 4NQO is an alkylating compound and potent mutagen that requires metabolic activation to be converted to 4-acetoxyaminoquinoline 1-oxide (4HAQO), which reacts with DNA causing damaging effects including single strand breaks, incomplete repair sites and alkali-labile sites.…”
Section: Discussionmentioning
confidence: 99%